Peningkatan Pemahaman Konsep Geometri melalui Visualisasi Sketsa Grafik Fungsi bagi Siswa Di SMA Negeri 1 Pujut - Abdurahim, Abdurahim; Robbaniyyah, Nuzla Af'idatur; Ramadhan, Hikmal Maulana; Hidayatullah, Azka Farris; Alfian, Muhammad Rijal; Bahri, Syamsul; Awalushaumi, Lailia; Syechah, Bulqis Nebula; Marwan, Marwan; Salwa, Salwa; Rusadi, Tri Maryono; Maharani, Andika Ellena Saufika Hakim; Harsyiah, Lisa; Baskara, Zulhan Widya; Satriyantara, Rio; Zulhan Widya Baskara (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2025)
Geometry is one of the fundamental topics in mathematics, playing a crucial role in understanding shapes, sizes, positions, and spatial relationships between objects. Mastery of this concept is essential; however, in practice, many students still struggle to grasp geometry material. This issue is also evident at SMA Negeri 1 Pujut, where several students demonstrate a low level of understanding of geometric concepts. In response to this problem, the aim of the research is a community service activity was carried out in the form of tutoring sessions focused on improving students' understanding of geometry. This activity employed a visualization approach through function graph sketches to help students better comprehend the interconnections between concepts in a more concrete way. Based on the evaluation results, data showed that 86.67% of students exhibited improved learning outcomes after participating in the activity. This achievement indicates that the instructional method used by the facilitators was quite effective and well-received by the majority of participants.